2017
DOI: 10.1039/c7dt00499k
|View full text |Cite
|
Sign up to set email alerts
|

Delocalized and localized donating–accepting Mn–C interactions in half-sandwich cyclopentadienyl and pentadienyl complexes

Abstract: The widely used cyclopentadienyl (Cp) ligand and the pentadienyl (Pdl) ligand have very similar molecular orbitals (MOs) but they have significantly different chemical behavior. The extensively mixing of the MOs in the Pdl ligand has prevented a quantitative explanation of the observed differences between these two ligands. In a series of synthesized close/open half sandwich manganese phosphine carbonyls, the quantum theory of atoms in molecules and the interacting quantum atom model allow us to quantify the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…The atomic quadrupole moments ( Q (Ω)) defined in the quantum theory of atoms in molecules (QTAIM) show a similar bonding scenario to that provided by the MO analyses. The components of the Q (Ω) tensor have previously been used to describe the π‐back‐donation of the linear carbonyl group to a metal center . The central carbon chain of cumulenes is linear like the carbonyl group, so it is possible to use Q (Ω) as a descriptor of back‐donation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The atomic quadrupole moments ( Q (Ω)) defined in the quantum theory of atoms in molecules (QTAIM) show a similar bonding scenario to that provided by the MO analyses. The components of the Q (Ω) tensor have previously been used to describe the π‐back‐donation of the linear carbonyl group to a metal center . The central carbon chain of cumulenes is linear like the carbonyl group, so it is possible to use Q (Ω) as a descriptor of back‐donation.…”
Section: Resultsmentioning
confidence: 99%
“…The components of the Q(W)t ensor have previously been used to describe the p-back-donation of the linear carbonyl group to a metal center. [52,53] The central carbonc hain of cumulenes is linear like the carbonyl group, soi ti sp ossible to use Q(W)a sa descriptor of back-donation. As in the case of the carbon atom in the CO group, the C2 atom in cumulenes has two Q(W)e igenvectors that are perpendicular to the C1ÀC2 bond (both with negative eigenvalues), one normalt ot he carbene plane (Q ??…”
Section: Resultsmentioning
confidence: 99%
“…[48] Several papers note the lack of bond critical points (BCPs) and AIL between metal and atoms of a ligand strongly interacting. [7,41,48] Other QTAIM indicators, such as the delocalization index (δ(A,B)) and the source function, have shown that the lack of BCPs does not mean that there is no interaction, and provide a better depiction for bond in organometallic compounds. In order to depict the MÀ Az bonding scenario in the presence of spectator ligands of different nature, we employed the delocalization index, δ(M,C), as a parameter related to the bond order that allowed us to suggest the hapticity of MÀ Az complexes.…”
Section: Resultsmentioning
confidence: 99%
“…These preferences can be affected by the spectator ligands because it has been shown that their electronic nature can drastically change the bonding capabilities of the metal centre. [38][39][40][41] Our work aims to understand how the nature of other ligands can affect the coordination preference of the metal to the Az ligand and how these ligands change the nature of the metal-Az bond.…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that IQA provides valuable information about energy redistribution that accompanies transformation of reactants into products, thus enabling to get a deeper insight into reaction mechanisms of a number of processes. Moreover, it provides valuable information concerning bonds' nature and properties, being also able to describe weak non‐covalent interactions . Proper description of weak interactions is important for the analysis presented in this contribution due to a mutual transformation between a hydrogen bond and a covalent bond.…”
Section: Introductionmentioning
confidence: 99%